Synergic Effect of Honey with Other Natural Agents in Developing Efficient Wound Dressings - Angela Spoială; Cornelia-Ioana Ilie; Denisa Ficai; Anton Ficai; Ecaterina Andronescu (MDPI AG, 2022)
Honey has been used for therapeutic and nutritional purposes since ancient times. It was considered one of the essential medical assets in wound healing. According to research, honeybees have significant antibacterial, antioxidant, anti-inflammatory, antitumor, and wound-healing properties. Lately, scientific researchers have focused on apitherapy, using bee products to protect and strengthen the immune system. Since honey is the most important natural product rich in minerals, proteins, and vitamins, it has been intensively used in such therapies. Honey has gained significant consideration because of the beneficial role of its antioxidant compounds, such as enzymes, proteins, amino and organic acids, polyphenols, and carotenoids, but mainly due to flavonoids and phenolic acids. It has been proven that phenolic compounds are responsible for honey's biological activity and that its physicochemical properties, antioxidants, and antimicrobial potential are significant for human health. The review also presents some mechanisms of action and the medical applications of honey, such as wound healing dressings, skin grafts, honey-based nanofibers, and cochlear implants, as the most promising wound healing tools. This extensive review has been written to highlight honey's applications in medicine; its composition with the most important bioactive compounds also illustrates its synergistic effect with other natural products having remarkable therapeutic properties in wound healing.